Myocardial fibrosis in patients with a history of Kawasaki disease. (February 2021) - Dusenbery, Susan M.; Newburger, Jane W.; Colan, Steven D.; Gauvreau, Kimberlee; Baker, Annette; Powell, Andrew J.
Abstract: Objectives: Cardiac magnetic resonance (CMR) measurements of myocardial extracellular volume fraction (ECV) and late gadolinium enhancement (LGE) in patients with a history of Kawasaki disease (KD) were analyzed to determine whether fibrosis was increased compared to controls. Methods: In this single center retrospective study, patients with KD who had a CMR with ECV measurement and LGE assessment were included. The ECV was calculated in the mid-left ventricle by measuring T1 values for blood pool and myocardium before and after gadolinium administration with a Look-Locker technique. CMR findings were compared to 20 control subjects. Results: KD patients (n = 13) had a median age at CMR of 14.9 years (range, 7.5–36.0). Control subjects (n = 20) had a median age at CMR of 16 years (range, 11.0–36.0). Twelve KD patients had coronary aneurysms. The KD patients had a significantly lower indexed LV mass (p = 0.03) and LV mass/volume ratio (p = 0.01). ECV was not significantly different in KD patients and controls (0.26 (range, 0.20–0.30) vs. 0.25 (range, 0.18–0.28), p = 0.28). One KD patient (8%) had an increased (>0.28) ECV. LGE indicating focal fibrosis was found in 5 of 13 (38%) of KD patients. Patients with LGE tended to have a higher maximum coronary dimension z-score (p = 0.09). Conclusions: In this study of KD patients, most of whom had aneurysms, ECV did not differ significantly from that in normal controls. Focal fibrosis based on LGE was common. Future larger studies should compare ECV in KD patients with and without aneurysms to define the risk of myocardial fibrosis after KD.